Half of Prescribed Antibiotics Are Not Needed: A Pharmacist-Led Antimicrobial Stewardship Intervention and Clinical Outcomes in a Referral Hospital in Ethiopia - Gebretekle, Gebremedhin Beedemariam; Haile Mariam, Damen; Abebe Taye, Workeabeba; Mulu Fentie, Atalay; Amogne Degu, Wondwossen; Alemayehu, Tinsae; Beyene, Temesgen; Libman, Michael; Gedif Fenta, Teferi; Yansouni, Cedric P.; Semret, Makeda (Frontiers in Public Health, 2020)
Intense antibiotic consumption in Low- and Middle-Income Countries (LMICs) is fueled by critical gaps in diagnostics and entrenched syndromic management of infectious syndromes. Few data inform the achievability and impact of antimicrobial stewardship interventions, particularly in Sub-Saharan Africa. Our goal was to demonstrate the feasibility of a pharmacist-led laboratory-supported intervention at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia, and report on antimicrobial use and clinical outcomes associated with the intervention. This was a single-center quasi-experimental study conducted in two phases: (i) an intervention phase (November 2017 to August 2018), during which we implemented weekly audit and immediate feedback on antibiotic prescriptions of patients admitted in 2 pediatric and 2 adult medicine wards, and (ii) a post-intervention phase (September 2018 to January 2019) during which we audited prescriptions but provided no feedback to the treating teams. The intervention was conducted by an AMS team consisting of 4 clinical pharmacists and one ID specialist. Our primary outcome was antimicrobial utilization (days of therapy (DOT) per 1000 patient-days and duration of antibiotic treatment courses); secondary outcomes were length of hospital stay (LOS) and in-hospital all-cause mortality. A multivariable logistic regression model was used to explore factors associated with all-cause in-hospital mortality. We collected data on 1,109 individual patients (707 during intervention, 402 post-intervention). Ceftriaxone, vancomycin, cefepime, and meropenem were the most commonly prescribed antibiotics; 96% of the AMS team's recommendations were accepted. We recommended to discontinue antibiotics in 54% of cases. Once the intervention ceased, total antimicrobial use increased by 51.6% and mean duration of treatment by 4.1 days/patient. Mean LOS and crude mortality increased significantly post-intervention (LOS: 19.8 vs 24.1 days; mortality 6.9% vs 14.7%). These differences remained significant after adjusting for potential confounders. A pharmacist-led AMS intervention focused on duration of antibiotic treatment was feasible with good acceptability in our setting. Cessation of audit-feedback activities was associated with immediate and sustained increase in antibiotic consumption, reflecting a rapid return to baseline (pre-intervention) prescribing practices, and worse clinical outcomes. Audit-feedback activities can effectively reduce antimicrobial consumption and result in better outcomes, but require organizational leadership’s commitment for sustainable benefits.